2004
DOI: 10.1002/aqc.620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow variation on channel and floodplain biota and habitats of the Sacramento River, California, USA

Abstract: ABSTRACT1. Despite progress in the development of conceptual models of river processes, the validation and application of these models to conservation may be limited by a deficit of tools for intermediate-scale (1-100 km) reaches. A model was developed to examine the effect of variation in flow on the responses of two trophic levels in a large temperate river (Sacramento River) and its seasonal floodplain (Yolo Bypass). Field data and hydrologic simulations were evaluated for three hydrologically diverse years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 54 publications
7
94
0
Order By: Relevance
“…This fact shows that these organisms have excellent colonizing abilities, rapid larval development (Wiggins et al, 1980;Higgins and Merritt, 1999;Sommer et al, 2004) and are adapted to the hydrological variability of this ecosystem. Besides, many Chironomidae species are resistant to desiccation and emerge from the sediment after few days of flooding (Benigno and Sommer, 2008;Tronstad et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This fact shows that these organisms have excellent colonizing abilities, rapid larval development (Wiggins et al, 1980;Higgins and Merritt, 1999;Sommer et al, 2004) and are adapted to the hydrological variability of this ecosystem. Besides, many Chironomidae species are resistant to desiccation and emerge from the sediment after few days of flooding (Benigno and Sommer, 2008;Tronstad et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In floodplains, larvae of the family Chironomidae can be the most abundant invertebrate group (Sommer et al, 2004;Benigno and Sommer, 2008). The Chironomidae community usually changes in response to physical and chemical variations of the water (Higuti and Takeda 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Periodic flooding of the Yolo Bypass has been well documented as providing benefits to many native species of fish and lower trophic levels (Sommer et al 2001a(Sommer et al , 2001b(Sommer et al , 2004. Even during drought conditions, infrastructure could be modified to allow flows to the east side of the bypass, along the Tule Canal and Toe Drain, stimulating primary and secondary production which could flow into the North Delta as far downstream as Suisun Bay.…”
Section: Yolo Bypassmentioning
confidence: 99%
“…Off-channel habitats such as river floodplains are frequently described as areas with high nutrient input, primary productivity, and prey abundance when compared to the main channel to which they connect (Bayley 1991;Sommer et al 2004;Limm and Marchetti 2009). Research suggests that off-channel habitats provide increased productivity due to a suite of environmental and ecological factors including: increased water temperature (Pease et al 2006), habitat heterogeneity (Sommer et al 2004), refuge areas with low velocity (Pease et al 2006), and an abundance of invertebrate prey (Gladden and Smock 1990;Limm and Marchetti 2009). Although a number of these characteristics were not measured in this study, Limm and Marchetti (2009) found that chironomid abundance was greater in both Mud Creek and nearby Toomes Creek than the main channel Sacramento River, suggesting that abundant invertebrate prey, perhaps coupled with increased water temperatures may be factors contributing to increased abundance, richness, and diversity of fish larvae in Mud Creek.…”
Section: Seasonal Versus Perennial Streamsmentioning
confidence: 99%
“…Thus, seasonal floodplains and other similar habitats peripheral to the mainstem of rivers and streams are increasingly recognized as important breeding and nursery areas for many species of freshwater fish (Turner et al 1994;Balcombe et al 2007). Seasonal inundation significantly increases the total amount of available aquatic habitat and provides greater habitat heterogeneity than is found in the main channel (Power et al 1995;Sommer et al 2002Sommer et al , 2004. Furthermore, the seasonal habitats generally offer slower, shallower, and warmer water (Turner et al 1994;Scheidegger and Bain 1995) than the mainstem.…”
mentioning
confidence: 99%